2022
DOI: 10.1038/s41467-022-32379-w
|View full text |Cite
|
Sign up to set email alerts
|

Conserved subcortical processing in visuo-vestibular gaze control

Abstract: Gaze stabilization compensates for movements of the head or external environment to minimize image blurring. Multisensory information stabilizes the scene on the retina via the vestibulo-ocular (VOR) and optokinetic (OKR) reflexes. While the organization of neuronal circuits underlying VOR is well-described across vertebrates, less is known about the contribution and evolution of the OKR and the basic structures allowing visuo-vestibular integration. To analyze these neuronal pathways underlying visuo-vestibul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 65 publications
4
32
0
Order By: Relevance
“…Instead, we find that vestibular projection neurons synapse on to extraocular motor neurons (Figure 6) well before those motor neurons synapse on to muscles 114 . Comparative approaches [115][116][117] could resolve the question of whether the temporal differences we observe are zebrafish-specific. Together, our work rejects the current model for vestibulo-ocular reflex ontogeny.…”
Section: Circuit Assembly: First-come First Served or Firstborn First...mentioning
confidence: 99%
“…Instead, we find that vestibular projection neurons synapse on to extraocular motor neurons (Figure 6) well before those motor neurons synapse on to muscles 114 . Comparative approaches [115][116][117] could resolve the question of whether the temporal differences we observe are zebrafish-specific. Together, our work rejects the current model for vestibulo-ocular reflex ontogeny.…”
Section: Circuit Assembly: First-come First Served or Firstborn First...mentioning
confidence: 99%
“… 83 , 113 Instead, we find that vestibular projection neurons synapse on to extraocular motor neurons ( Figure 6 ) well before those motor neurons synapse on to muscles. 114 Comparative approaches 115 117 could resolve the question of whether the temporal differences we observe are zebrafish specific. Together, our work rejects the current model for vestibulo-ocular reflex ontogeny.…”
Section: Discussionmentioning
confidence: 99%
“…Another visually-driven behavior often compared to insect optomotor response is optokinetic nystagmus (OKN) (Hardcastle and Krapp, 2016). OKN is a syn-directional eye movement triggered by optic flow, which is found across vertebrates from jawless fish (Wibble et al, 2022) to humans (Dodge, 1903;Dodge and Fox, 1928), as well as in arthropods (Fenk et al, 2022) and cephalopods (Messenger, 1970). Similar to rotational vection, it has been found that vertical stationary patterns can strongly suppress OKN in humans (Murasugi et al, 1989(Murasugi et al, , 1986.…”
Section: Geometrical Negative Evidence Against Self Rotation In Diffe...mentioning
confidence: 99%